2006
DOI: 10.1002/chem.200600599
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Cyclodepsipeptide Apratoxin A and Its Analogues and Assessment of Their Biological Activities

Abstract: A novel total synthesis of apratoxin A is described, with key steps including the assembly of its ketide segment through a D-proline-catalyzed direct aldol reaction and Oppolzer's anti aldol reaction and the preparation of its thiazoline unit in a biomimetic synthesis. An oxazoline analogue of apratoxin A has also been elaborated by a similar approach. This compound has a potency against HeLa cell proliferation only slightly lower than that of apratoxin A, whilst a C(40)-demethylated oxazoline analogue of apra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 51 publications
3
41
0
2
Order By: Relevance
“…Wipf and Uto elegantly demonstrated that the oxazoline moiety was ringopened to the corresponding thioamide on a cyclic peptide by treatment with H 2 S, and then dehydrative cyclization using N,N-dimethylaminosulfur trifluoride (DAST) led to the total synthesis of the thiazoline-containing cyclic peptide trunkamide A. 13) We initially synthesized the oxazoline analogue of apratoxin A (16) 7,14,15) and attempted to convert the oxazoline moiety to a thiazoline ring. triazol-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HATU)/N,N-diisopropylethylamine (DIEA)), gave undesired azlactone 10 in 49% yield, along with the desired tetrapeptide 9 in only 21% yield.…”
Section: Apratoxin Amentioning
confidence: 99%
See 1 more Smart Citation
“…Wipf and Uto elegantly demonstrated that the oxazoline moiety was ringopened to the corresponding thioamide on a cyclic peptide by treatment with H 2 S, and then dehydrative cyclization using N,N-dimethylaminosulfur trifluoride (DAST) led to the total synthesis of the thiazoline-containing cyclic peptide trunkamide A. 13) We initially synthesized the oxazoline analogue of apratoxin A (16) 7,14,15) and attempted to convert the oxazoline moiety to a thiazoline ring. triazol-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HATU)/N,N-diisopropylethylamine (DIEA)), gave undesired azlactone 10 in 49% yield, along with the desired tetrapeptide 9 in only 21% yield.…”
Section: Apratoxin Amentioning
confidence: 99%
“…The oxazoline analogue of apratoxin A (16) was also so potent that the thiazoline ring could be replaced by an oxazoline ring, as also reported by Ma's group. 15) Protection of the hydroxy group with a TES group, or removal of all substituents from the hydroxy acid moiety, led to a loss of cytotoxicity. Azido-containing analogues 41-45 exhibited potent cytotoxicity.…”
Section: Solid-phase Assisted Synthesis Of Apratoxin a And Its Analogmentioning
confidence: 99%
“…通过比 对分析, apratoxin A 的构效关系(图 4)也可从中窥得一 斑 [18,19] . [3] 0.36 [3] 1.4 [20] 10 [20] /2.2 [7] /190 [9] 10 [20] 5.97 [21] /1.21 [18] 2.5 [19] 70 21.3 [22] 10.8 [22] 71 1.0 [22] 0.73 [22] 72 2.6 [23] 73 21 [20] 72 [20] 59 [20] 184 [21] 74 4.92 [21] 2 [18] 75 14 [18] 76 3.4 [19] 77 89.9 [19] 78 37.6 [22] 85.1 [22] 41 [20] 121 [20] 160 [20] 79 9.7 [7] /380 [9] 80 920 [7] 81 >10000 [7] 82 >10000 [7] 83 1.14 [21] 84 258 [21] 85 1.58 [21] 86 373 [21] 87 4.15 [21] 88 1700 [21] 89 28000 [9] 90 450 [9] 91 2100 [9] 92 1700 [9] 93 80 [9] 94 350 [9] 95 30 [9] 3...…”
Section: Methodsmentioning
confidence: 99%
“…[78] и обладающие цитотоксичностью in vitro против различных опухолевых клеток человека и животных. [79] В литературе [30,[80][81][82] представлены синтезы только апратоксина А (152), один из которых [81] основан на макролактамизации ациклического предшественника 153, доступного при сочетании двух блок-синтонов 154 и 155 (Cхема 39).…”
Section: синтез противоопухолевого агента апротоксина Aunclassified
“…Соединение 154 представляет из себя тетрапептид, полученный инициируемым с помощью гексафторфосфата (7-азабензотриазол-1-илокси)трипир-ролидинфосфония (PyAOP) сочетанием производных изолейцина (156), аланина (157), тирозина (158) и цистеина (159) [82] (Cхема 40). Синтон 155 получен из оптически активного непредельного спирта 160 -продукта асимметрической конденсации изокамфеилаллилборана с трет-амиловым альдегидом по Брауну.…”
Section: синтез противоопухолевого агента апротоксина Aunclassified